THE JURIDICAL REVIEW OF INTERFAITH MARRIAGE IS LINKED TO LAW NUMBER 1 OF 1974 CONCERNING MARRIAGE AS AMENDED BY LAW NUMBER 16 OF 2019 CONCERNING MARRIAGE - Adinda Silvia Febrianty; Gagarin Akbar, Muhamad Gary; Abas, Muhamad (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2024)
Indonesia is known for its diverse cultural customs that have been embedded from their previous ancestors and different religions and beliefs. Of course, each has different rules. Similar to marriage, the variety of religions and streams of belief in Indonesia does not rule out the possibility of interfaith marriage. Interfaith marriages are marriages performed by people of different religions or different beliefs. The issues raised in this study are how the validity of interfaith marriage according to Law Number 1 of 1974 concerning Marriage has been amended by Law Number 16 of 2019 concerning Marriage and how the judge's consideration in granting requests for different religions in the study of decision number 916 / Pdt.P / 2022 / PN. Sby. The purpose of this study is to determine the validity of interfaith marriage according to Law Number 1 of 1974 concerning Marriage and to find out the judge's consideration in granting an interfaith marriage request in the study of decision Number 916/Pdt.P/2022/PN. Sby. This research is a type of qualitative research that uses a normative juridical approach method, namely the approach of research by researching and reviewing the object of research through literature study. The author's conclusion to the decision is that there is an imbalance or inconsistency with Law Number 1 of 1974 concerning Marriage, that in article 2 paragraph (1) of Law Number 1 of 1974 concerning Marriage states that marriage is valid, if it is carried out according to the laws of each religion and belief.